Plasmonic performance of AuxAgyCu1−x−y alloys from many-body perturbation theory. (22nd May 2019) - Orhan, Okan K; O'Regan, David D
Abstract: We present a detailed appraisal of the optical and plasmonic properties of ordered alloys of the form Aux Agy Cu1-x-y, as predicted by means of first-principles many-body perturbation theory augmented by a semi-empirical Drude–Lorentz model. In benchmark simulations on elemental Au, Ag, and Cu, we find that the random-phase approximation (RPA) fails to accurately describe inter-band transitions when it is built upon semi-local approximate Kohn–Sham density-functional theory band-structures. We show that non-local electronic exchange-correlation interactions sufficient to correct this, particularly for the fully-filled, relatively narrow d -bands which contribute strongly throughout the low-energy spectral range (0–6 eV), may be modeled very expediently using band-stretching operators that imitate the effect of a perturbative self-energy correction incorporating quasiparticle (QP) mass renormalization. We thereby establish a convenient work-flow for carrying out approximated spectroscopic calculations on alloys and, in particular here, we have considered alloy concentrations down to 12.5% in, including all possible crystallographic orderings of face-centred cubic type. We develop a pragmatic procedure for calculating the Drude plasmon frequency from first principles, including self-energy effects, as well as a semi-empirical scheme for interpolating the plasmon inverse lifetimes between stoichiometries. A distinctive M-shaped profile is observed in both quantities for binary alloys, in qualitative agreement with previous experimental findings. A range of optical and plasmonic figures of merit are discussed, and plotted for ordered at three representative solid-state laser wavelengths. On this basis, we predict that certain compositions may offer improved performance over elemental Au for particular application types. We predict that while the loss functions for both bulk and surface plasmons are typically diminished in strength through binary alloying, certain stoichiometric ratios may exhibit higher-quality (longer-lived) localized surface-plasmons and surface-plasmon polaritons, at technologically-relevant wavelengths, than those in elemental Au.